China's Nobel boycott victory claim hollow. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2011)
The article focuses on the controversy regarding the Norwegian Nobel Committee's decision to award the Peace Prize to former-Chinese academic and democracy activist Liu Xiaobo in Norway. It states that Xiaobo was given a standing ovation by more than 1,000 ambassadors due to his fight for democracy, rule of law, and respect for human rights. However, the government in China has condemned the prize and suspended its diplomatic contract with Norway.